2011
DOI: 10.1016/j.ajpath.2011.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stimulation of VEGFR2 Accelerates Progressive Renal Disease

Abstract: Vascular endothelial growth factor A (VEGF-A) can play both beneficial and deleterious roles in renal diseases, where its specific function might be determined by nitric oxide bioavailability. The complexity of VEGF-A in renal disease could in part be accounted for by the distinct roles of its two receptors; VEGFR1 is involved in the inflammatory responses, whereas VEGFR2 predominantly mediates angiogenesis. Because nondiabetic chronic renal disease is associated with capillary loss, we hypothesized that selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 54 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…Our previous studies demonstrated that the VEGFR2/caveolin-1 association plays an important role in ECM accumulation in mesangial cells [23] . Recent studies have demonstrated that selective stimulation of VEGFR2 accelerates progressive renal disease [42] . Thus, we investigated the effects of fasudil on the association between VEGFR2 and caveolin-1 within the diabetic renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that the VEGFR2/caveolin-1 association plays an important role in ECM accumulation in mesangial cells [23] . Recent studies have demonstrated that selective stimulation of VEGFR2 accelerates progressive renal disease [42] . Thus, we investigated the effects of fasudil on the association between VEGFR2 and caveolin-1 within the diabetic renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney injury induced by angiotensin II infusion followed by a high-salt diet, administration of VEGF-A 121 did not improve PTC rarefaction [79]. In addition, VEGF-A 121 treatment did not improve PTC rarefaction in neonatal mouse kidneys subjected to UUO [80], and systemic overexpression of a mutant form of VEGF-A that can bind only to VEGFR-2 but not to VEGFR-1 enhanced glomerular injury as well as interstitial fibrosis in mice with uninephrectomy [81]. Furthermore, the timing of angiogenic treatment is crucial.…”
Section: Considerations For Therapy To Limit Ptc Rarefaction In Ckdmentioning
confidence: 99%
“…VEFG-R2 is one of the receptors of vascular endothelial growth factor A (VEGF-A), which plays an important role in renal disease. Despite many studies that reported VEGF-A to be beneficial in several types of renal injury [37,20,21,35], stimulation of VEGF-R2, however, may be associated with renal injury as it is found to increase in damaged tubular epithelial cells and caused angiogenesis in the kidney [31]. …”
Section: Discussionmentioning
confidence: 99%